Coatings and Thin-Film Technologies - Andres Perez-Taborda, Jaime; Avila Bernal, Alba G. (IntechOpen, 2019)
The field of coatings and thin-film technologies is rapidly advancing to keep up with new uses for semiconductor, optical, tribological, thermoelectric, solar, security, and smart sensing applications, among others. In this sense, thin-film coatings and structures are increasingly sophisticated with more specific properties, new geometries, large areas, the use of heterogeneous materials and flexible and rigid coating substrates to produce thin-film structures with improved performance and properties in response to new challenges that the industry presents. This book aims to provide the reader with a complete overview of the current state of applications and developments in thin-film technology, discussing applications, health and safety in thin films, and presenting reviews and experimental results of recognized experts in the area of coatings and thin-film technologies.